Languages of loss and mourning beyond (the) borders: Bosnia - Stanković, Snežana (Aegean Working Papers in Ethnographic Linguistics, 2019)
The following paper deals with the language of commemoration of refugee women from ex-Yugoslavia, mainly Bosnia who escaped to Berlin during or after the violent conflicts in the 1990s. Handkerchiefs, personalised with names, birth and death dates of deceased family members, have arisen out of the embroidery therapy they have undertaken. These artefacts all resemble each other in that they recount the trauma of the loss of the beloved dead, whose remains were either found and then reburied, or the dead who remained missing. This micro-study aims at analyzing the verbal and visual means of expression employed by the refugee women in their embroidery. In treating language as a semiotic composition of oral and written verbal communication, image, sound, and movement, it leaves sociolinguistic discussions on the national languages which have emerged in the region behind and delves into the expression of loss and mourning inscribed on the handkerchiefs.